2021
DOI: 10.1002/jsfa.11108
|View full text |Cite
|
Sign up to set email alerts
|

Response of area‐ and yield‐scaled N2O emissions from croplands to deep fertilization: a meta‐analysis of soil, climate, and management factors

Abstract: BACKGROUND Nitrous oxide (N2O) is an important and persistent greenhouse gas making a significant contribution to global climate change. Deep fertilization has been demonstrated to increase crop yield and nutrient use efficiency by decreasing losses of volatilization and surface runoff. However, N2O emissions from croplands induced by deep fertilization are variable and mitigation strategies remain uncertain. This study aimed to (i) quantify the response of area‐scaled (N2O emissions) and yield‐scaled N2O emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Previous field studies have shown that deep fertilizer placement, compared to a broadcast application, increased yields, improved NUE, and decreased N runoff . Regarding N2O emissions, however, results are somewhat contradicting: while deep N fertilizer placement effectively lowered N2O emissions in rice paddies and in field experiments in upland regions (e.g., Chen et al 2021, Pandit et al 2022, as well as in combination with conservation tillage methods Nash et al 2012), other studies (e.g. ) found that N2O emissions were higher from deeper N placement compared to shallow N placement.…”
Section: Introductionmentioning
confidence: 96%
“…Previous field studies have shown that deep fertilizer placement, compared to a broadcast application, increased yields, improved NUE, and decreased N runoff . Regarding N2O emissions, however, results are somewhat contradicting: while deep N fertilizer placement effectively lowered N2O emissions in rice paddies and in field experiments in upland regions (e.g., Chen et al 2021, Pandit et al 2022, as well as in combination with conservation tillage methods Nash et al 2012), other studies (e.g. ) found that N2O emissions were higher from deeper N placement compared to shallow N placement.…”
Section: Introductionmentioning
confidence: 96%
“…Ideally, good management strategies should be identified that allow N 2 O emissions to be reduced while largely maintaining or even increasing crop yields, i.e., the relatively lower yield‐scaled N 2 O emissions. In recent decades, many individual field studies and meta‐analyses have been conducted to investigate the effects of land use and its managements on various crop production and GHG emissions or yield‐scaled GHG emissions (e.g., Chen et al., 2021; Guo et al., 2022; Kim et al., 2023; Kim & Giltrap, 2017; Qin et al., 2012; Sainju, 2016; Shang et al., 2021; Yang et al., 2019; Zhang, Tian, et al., 2020). The findings of these studies highlight that yield‐scaled GHG emissions are an excellent indicator for assessing the environmental efficiency of a cropping system.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, what qualifies as a deep placement depth can differ widely, depending on the existing local practice for fertilization for the particular cropping system. Although placement depth, as well as climate and growing systems vary, deep N placement relative to surface fertilization has been reported to increase yields and NUE, decrease ammonification, and in some cases decrease N 2 O emissions (Chen et al 2021;Pandit et al 2022;Rychel et al 2020;Sosulski et al 2020;Wu et al 2021;Zhang et al 2022;). However, NO 3 − remaining in the soil after crop uptake is susceptible to leaching and literature on the fate of NO 3 − following deep fertilization is scant.…”
Section: Introductionmentioning
confidence: 99%